If XY=-6, what is the value of XY(X+Y)?
The book says the answer is B. I get D, as with #1, you can deduce Y to be -2 or -3 making X+Y=-5 regardless. Can anybody explain why/how 1) does not work?
Since xy=-6, y=-6/x
Replacing the value of x in stat 1 and solving the quadratic equation x^2-5x+6=0 we get x=2 or x=3 which means that y=-3 or y=-2 (since xy=-6)
Using x=2 and y=-3 gives us a different value for xy(x+y) than using x=3 and y=-2; Insufficient
From the stem we get x=-6/y
From stat 2 we get x=18/y^2
Solving for y we get y=-3 meaning that x=2; suff